Effect of Single Housing on Innate Immune Activation in Immunodeficiency Virus–Infected Pigtail Macaques (Macaca nemestrina) as a Model of Psychosocial Stress in Acute HIV Infection. Issue 8 (7th October 2022) - Castell, Natalie; Guerrero-Martin, Selena M.; Rubin, Leah H.; Shirk, Erin N.; Brockhurst, Jacqueline K.; Lyons, Claire E.; Najarro, Kevin M.; Queen, Suzanne E.; Carlson, Bess W.; Adams, Robert J.; Morrell, Craig N.; Gama, Lucio; et al.
ABSTRACT: Objective: Simian immunodeficiency virus (SIV) infection of macaques recapitulates many aspects of HIV pathogenesis and is similarly affected by both genetic and environmental factors. Psychosocial stress is associated with immune system dysregulation and worse clinical outcomes in people with HIV. This study assessed the impact of single housing, as a model of psychosocial stress, on innate immune responses of pigtailed macaques ( Macaca nemestrina ) during acute SIV infection. Methods: A retrospective analysis of acute SIV infection of 2- to si6-year-old male pigtailed macaques was performed to compare the innate immune responses of socially ( n = 41) and singly ( n = 35) housed animals. Measures included absolute monocyte count and subsets, and in a subset ( n ≤ 18) platelet counts and activation data. Results: SIV infection resulted in the expected innate immune parameter changes with a modulating effect from housing condition. Monocyte number increased after infection for both groups, driven by classical monocytes (CD14 + CD16 − ), with a greater increase in socially housed animals (227%, p < .001, by day 14 compared with preinoculation time points). Platelet numbers recovered more quickly in the socially housed animals. Platelet activation (P-selectin) increased by 65% ( p = .004) and major histocompatibility complex class I surface expression by 40% ( p = .009) from preinoculation only in socially housed animals, whereas no change in these measures occurred in singly housed animals. Conclusions: Chronic psychosocial stress produced by single housing may play an immunomodulatory role in the innate immune response to acute retroviral infection. Dysregulated innate immunity could be one of the pathways by which psychosocial stress contributes to immune suppression and increased disease severity in people with HIV.